Bacteriological assessment of pipe-borne, borehole, and well water sources available to students in Nasarawa State University Keffi, Nasarawa State, Nigeria - Etido Udoh Elijah (Sustinere: Journal of Environment and Sustainability, 2023)
The provision of clean water, microorganisms-free water is crucial in preventing the transmission of waterborne diseases. This study was conducted with the objective of evaluating the bacteriological quality of water sources accessible to students within Nasarawa State University Keffi. Sixteen samples, comprising ten from piped source, three from boreholes, and three from wells, were subjected to bacteriological quality assessment. The total bacterial count was analyzed using the pour plate technique, while the total coliform count and bacteriological index were assessed through the most probable number technique. Among the various water sources examine, pipe-borne water exhibited the lower bacterial contamination with a mean of 0.6×106 CFU/100 mL in contrast to borehole and well water sources, which recorded mean of 1.6×106 and 3.2×106 CFU/100 mL, respectively. Additionally, pipe-borne water demonstrated the lowest mean total coliform count, registering 22 MPN/100 mL. Notably, Notably, the water samples were found to harbor bacteria such as Escherichia coli, Klebsiella pneumonia, Enterobacter aerogens, and Citrobacter sp.  Alarming findings from this study highlight the unsuitability of most water samples for human consumption, as they fail to meet the quality standards established by the World Health Organization. Consequently, it is necessary to implement measures aimed at safeguarding water sources from contamination and curbing the proliferation of diseases. Furthermore, it is pertinent to prioritize adequate treatment of domestic water sources prior to consumption to ensure public health and well-being.